Synthesis of γ-N-modified 8-oxo-2’-deoxyguanosine triphosphate and its characterization - Thavoncharoensub, Ninticha; Maruyama, Kento; Heh, Choon Han; Leong, Kok Hoong; Shi, Hui; Shigematsu, Yoshiharu; Sasaki, Shigeki; Taniguchi, Yosuke (Taylor & Francis, 2019)
8-OxodGTP is generated by the reaction between dGTP and reactive oxygen species and a considered mutagenic nucleotide. It can be incorporated into the duplex DNA during replication processes by the DNA polymerase, and thus the repair enzyme removes oxodGTP from the nucleotide pools in living cells. On the other hand, the γ-modified triphosphates show interesting properties for use as biological tools. Therefore, the γ-N-pyrenylalkyl-oxodGTP derivatives were synthesized and their effect on the enzymatic reactions were evaluated. The γ-N-pyrenylmethyl-oxodGTP was found to be accepted by the DNA polymerase just like oxodGTP, but showed a competitive inhibition property for the human oxodGTPase. © 2019, © 2019 Taylor & Francis Group, LLC.